Peranan Aparatur Pemerintah Desa Dalam Pelayanan Masyarakat di Desa Pitu Kecamatan Tobelo Tengah Kabupaten Halmahera Utara - Aler, Yeilan Stasia; Rumapea, Patar; Ogotan, Martha (Sam Ratulangi University, 2016)
ABSTRACT: Services will be as good as village government officials can play a direct role and be involved inproviding services to the public in accordance with the duties and functions, so that people are satisfied with theservices provided by the village government and services expected to run optimally. This research is located inthe village Pitu Tobelo District of Central Halmahera north. The purpose of this study was to determine andidentify the role of village government apparatus in public services and constraints in the public service.The method used in this research is qualitative method. Informants were taken from various relatedelements, namely the head of the village and the Irish village and community shop. This study uses datacollection techniques: interview, observation and documentation. The steps in the analysis of the data is datareduction, data presentation and conclusion.From the results of this study indicate Role of Government Agencies in the village of Pitu in providingthe service is still not optimal. Judging from some of the constraints in the implementation of public services:Simplicity procedures, clarity, completeness of facilities and infrastructure, discipline politeness andfriendliness, comfort. 4 indicator shows inferior services and one indicator shows pretty good service. So overallit can be concluded that the existing services in the village Pitu still not running optimally.Keywords. Role of Government Personnel village in Public Service